×Senecurio, a new nothogenus for the hybrid ×S. kleiniiformis (Asteraceae subfam. Asteroideae tr. Senecioneae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2020)
As comprehensively argued by Ozerova et al. (2017), commonly cultivated South African material widely known as Senecio kleiniiformis Suessenguth (1937: 45), (Asteraceae subfam. Asteroideae tr. Senecioneae) (Fig. 1) represents an intergeneric hybrid derived from a species of Curio Heath (1997: 136) and Senecio tropaeolifolius MacOwan ex Mueller (1867: 242).